2010
DOI: 10.1021/nn9016108
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Outskirts of Fe and Co Catalyst Particles in Alumina-Supported Catalytic CVD Carbon Nanotube Growth

Abstract: Using thermal CVD, the synthesis of multi-walled carbon nanotubes exhibiting roots anchored directly onto ␣-alumina supports, rather than the catalyst particle, is reported. At such roots, the alignment of the graphitic planes with the support lattice fringes depends on the support crystal structure and orientation.Surface defects may alter the reactivity of the surface or control the anchoring of supported atoms or nanoparticles.We argue this surface defect is provided by the catalyst particle's edge interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…Whilst the studies showed a good correlation between the initial catalyst size and the CNT outer diameter, after synthesis the catalyst particles are found to lie within the core of the CNT and are elongated [42]. In addition, the roots of the graphitic walls do not terminate on the metal particle but rather on the oxide support as shown in Figure 5[43]. This highlights the diversity with which carbon nanotubes can grow, in that some base growth modes show the CNT is rooted at the metal catalyst particle [44] much like tip growth grown CNT [45] or in other cases from the oxide support [42,43].…”
Section: Hybrid Metal/metal-oxide Catalyst Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst the studies showed a good correlation between the initial catalyst size and the CNT outer diameter, after synthesis the catalyst particles are found to lie within the core of the CNT and are elongated [42]. In addition, the roots of the graphitic walls do not terminate on the metal particle but rather on the oxide support as shown in Figure 5[43]. This highlights the diversity with which carbon nanotubes can grow, in that some base growth modes show the CNT is rooted at the metal catalyst particle [44] much like tip growth grown CNT [45] or in other cases from the oxide support [42,43].…”
Section: Hybrid Metal/metal-oxide Catalyst Systemsmentioning
confidence: 99%
“…The right micrograph is a copy of the middle image with lines added to highlight the alignment of the graphitic planes with the rhombohedral (110) lattice fringes of the corundum support. Reprinted from Rümmeli et al [43]. …”
Section: Hybrid Metal/metal-oxide Catalyst Systemsmentioning
confidence: 99%
“…AAO templates can also function as catalysts for CNT deposition [17]. Therefore, metal-filled CNTs can be grown within the template, either before or after the deposition of ferromagnetic material inside the pores.…”
Section: Introductionmentioning
confidence: 99%
“…Nano-sized clusters and particles are attracting much attention for both fundamentally and technologically due to their unique properties [1][2][3][4][5]. Metal clusters on oxide substrates are of particular interest due to their applicability in nanomagnetism, catalysis, and so on.…”
Section: Introductionmentioning
confidence: 99%